Discovery of N-glycan Biomarkers for the Canine Osteoarthritis - Hyunjun Lee; Ahyun Lee; Nari Seo; Jiwon Oh; Oh-Kyeong Kweon; Hyun Joo An; Jaehan Kim (Life, 2020)
Protein glycosylation is a post-translational modification that impacts on protein activity, stability, and interactions. It was sensitively altered by the cellular state and, therefore, is now used for a diagnostic or prognostic indicator of various human diseases such as cancer. To evaluate the clinical feasibility in the veterinary area, the N-glycan biomarkers were discovered from canine serum for the diagnosis of osteoarthritis (OA), which is one of the most common diseases of dogs. N-glycome was obtained from 20 μL of canine serum by the enzymatic cleavage followed by the purification and enrichment using solid-phase extraction. Independent compositions of 163 and 463 N-glycans were found from healthy control (n = 41) and osteoarthritis patients (n = 92), respectively. Initially, 31 of the potential biomarkers were screened by the p-values below 1.0 × 10−10 from ANOVA. Then, the area under the curve (AUC) and the intensity ratio between OA patient and healthy control (P/C ratio) were calculated. Considering the diagnostic efficacy, the AUC bigger than 0.9 and the P/C ratio larger than 3.0 were used to discover 16 N-glycans as diagnostic biomarkers. Particularly, five of the diagnostic biomarkers were AUC above 0.99 and three of N-glycans had AUC 1.0. The results suggest a clear possibility for N-glycan biomarkers to be used as a clinical tool in the veterinary medical area enabling to provide objective and non-invasive diagnostic information.